Feature selection methods for big data bioinformatics: A survey from the search perspective - Wang, Lipo; Wang, Yaoli; Chang, Qing (Methods (San Diego, Calif.), 2016)
This paper surveys main principles of feature selection and their recent applications in big data bioinformatics. Instead of the commonly used categorization into filter, wrapper, and embedded approaches to feature selection, we formulate feature selection as a combinatorial optimization or search problem and categorize feature selection methods into exhaustive search, heuristic search, and hybrid methods, where heuristic search methods may further be categorized into those with or without data-distilled feature ranking measures.